Serotypes and antimicrobial resistance of Campylobacter jejuni isolated from humans and animals in Thailand - Sumalee Boonmar (2018)
We investigated the serotypes, distributions, and antimicrobial resistance of Campylobacter jejuni isolates from humans and animals as a source of infection in poultry between 2002 and 2003. A total of 50 C. jejuni isolates from humans and 29 C. jejuni isolates from poultry were studied for serotype using the Penner serotyping scheme and the drug susceptibilities of the isolates which were determined for 7 antimicrobial drugs using the disk diffusion method. Serotype B (10%), serotype E (8%) and serotype R (8%) were found in humans isolates, while serotype A (27%) was most freguently isolated from poultry, followed by serotype K (21%) and serotype C (13%). Resistance in human isolates to cephalothin was high (100%). Resistance to trimethoprim/ sulfamethoxazole, ciprofloxacin, and nalidixic acid were observed in 90, 82 and 78% of isolates, respectively. Most of the isolates (88%) were susceptible to erythromycin. High levels of resistance to drugs (ciprofloxacin and nalidixic acid) were observed in the isolates from poultry. These results indicate the importance of poultry as a reservoir of C. jejuni infection in Thailand is limited. In addition, a high proportion of the isolates were resistant to antimicrobial drugs, particularly the quinolone group.